Covered stent versus bare-metal stents for chronic total occluded long complicated femoropopliteal lesions: A 2-year single center review. Issue 1 (January 2019) - Lin, Ting-Chao; Chen, Po-Lin; Lee, Chiu-Yang; Shih, Chun-Che; Chen, I-Ming
Abstract : Background: To compare the efficacy, safety, and results of Viabahn versus bare-metal stents (BMS) in chronic total occluded (CTO) long femoropopliteal lesions. Methods: From April 2009 to August 2014, a total 97 patients (71.2 ± 9.7, 45–90 years old, 70 males) with occluded femo-ropopliteal lesions underwent Viabahn (55 patients) or BMS (42 patients) implantation. The clinical findings, procedural factors, and overall outcomes were collected and analyzed. Results: The average lesion length was 22.1 ± 4.8 cm in the Viabahn group and 17.8 ± 3.3 cm in the BMS group. Both groups had a 100% technical success rate. Although there was no difference between the groups in complication, mortality, and major amputation rates, the Viabahn group had a significantly better average post-operative ankle brachial index (ABI) at 1-year and 2-year follow-ups. The Viabahn group also had significantly less in-stent restenosis (ISR) and target lesion revascularization (TLR) compared with the BMS group. Nevertheless, the two groups shared similar 2-year primary patency rates (63.6% vs. 50.0%, p = .178) and 2-year secondary patency rates (85.5% vs. 81.0%, p = .554). Conclusion: Both Viabahn and BMS were efficient treatments for long femoropopliteal CTO lesions. However, the Viabahn group had significantly improved results compared with the BMS group in TLR and ISR, but the difference was not sufficient enough to result in different primary and secondary patency rates.